Electronic consultation as an alternative to hospital referral for patients with chronic kidney disease: a novel application for networked electronic health records to improve the accessibility and efficiency of healthcare. Issue 5 (16th June 2010) - Stoves, John; Connolly, John; Cheung, Chee Kay; Grange, Angela; Rhodes, Penny; O'Donoghue, Donal; Wright, John
Abstract : Problem: Chronic kidney disease is increasingly recognised in the UK, leading to a greater demand for specialist services. Traditional means of meeting this demand rely on GP referral of patients to see a nephrologist. Hospital assessment may be inconvenient for patients and inefficient for health services. Setting: 17 general practices and a secondary care nephrology service in Bradford, UK. Design: A before and after evaluation comparing nephrology referrals from implementation and non-implementation practices following the introduction of electronic consultations (e-consultations) for chronic kidney disease. Key measures for improvement: The number, appropriateness and quality of new referrals (paper and electronic) from primary care, the timeliness of responses and the satisfaction of patients and health professionals with the new service. Strategies for change: Electronic sharing of primary care electronic health records with the nephrology service was introduced to implementation practices. Participating GPs attended education workshops and received paper and e-guidance about the new service. Effects of change: There was a significant reduction in paper referrals from implementation practices. E-consultation provided nephrologists with access to more clinical information. GPs reported that the service was convenient, provided timely and helpful advice, and avoided outpatient referrals. Specialist recommendations were well followed, and GPs felt more confident about managing chronic kidney disease in the community. Lessons learnt: E-consultation promotes effective management of patients with mild-to-moderate chronic kidney disease in primary care, allowing specialist resources to be directed towards supporting patients with more complex needs. There is a potential role for e-consultation in other chronic disease specialties.